Continuous Activation of Dopamine Receptors Alleviates LPS-Induced Liver Injury in Mice via β-arrestin2 Dependent Akt/NF-κB Pathway - Li, Mingan; Zhang, Ce; Zhou, Lin; Sun, Xiaohui; Wang, Tian; Fu, Fenghua (Frontiers in Pharmacology, 2022)
Many studies showed that dopamine receptors (DRs) agonists have anti-inflammatory effects. Rotigotine, a non-ergot dopamine receptor agonist, mainly actives DRD2/DRD3/DRD1. Rotigotine extended-release microspheres (RoMS) are a sustained-release formulation that can release continuously rotigotine for more than 7 days after a single dose of RoMS. This study aimed to investigate whether RoMS can attenuate the lipopolysaccharide (LPS)-induced liver injury of mice. The liver injury was evaluated by assaying serum transaminase and observing histopathological changes. The levels of pro-inflammatory cytokines in serum were also detected. Western blot was employed to assay the expression of proteins in the Akt/NF-κB pathway. The results showed that pre-administration with a single dose of RoMS could inhibit the increase of serum transaminase induced by LPS, alleviate the pathological damage of liver tissue, and decrease the levels of tumor necrosis factor-α and interleukin-6. In addition, RoMS decreased Toll-like receptor 4 protein expression in liver tissue. RoMS mitigated liver injury by activating DRs and negatively regulating the β-arrestin2-dependent Akt/NF-κB signaling pathway. In conclusion, activation of DRs inhibited the releases of the LPS-induced pro-inflammatory cytokines and alleviated the immune-mediated liver injury in mice. The anti-inflammatory mechanism of RoMS may be related to the regulation of the β-arrestin2-dependent Akt/NF-κB signaling pathway.